An experimental study on granular dissipation for the vibration attenuation of skis - Bajkowski, J. M.; Dyniewicz, B.; Bajer, C. I.; Bajkowski, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Due to the continuous deformations and irregularities of the surface of snow, alpine skis exhibit dynamic excitation, leading to drastic vibrations and decreased manoeuvrability. Therefore, attenuating these unwanted vibrations, while ensuring that the ski experience is not compromised, is an important challenge. The possibility of using granular material in a damping device is studied in this paper. A container that was partially filled with loose granules was fixed at the tip of an alpine ski to suppress vibrations by dissipating energy through collisions. The performance was verified experimentally by studying the transient response of a ski mounted in a horizontal cantilever orientation. Moreover, on-snow tests were performed. Different numbers of plastic granules were used as a dissipating material. To identify the nonlinear damping characteristics of the system, a Hilbert transform was used. In the laboratory test, the displacement amplitude decay was up to 16 percentage points higher when a granular dissipator was attached to the ski than without the damper. During field testing, acceleration amplitudes were 9% lower compared to the ski without the dissipator. This solution could possibly be adapted to other boardsports on a wide variety of terrain, including ground, water and snow.